Symbiosis Specificity of the Preceding Host Plant Can Dominate but Not Obliterate the Association Between Wheat and Its Arbuscular Mycorrhizal Fungal Partners - Campos, Catarina; Carvalho, Mário; Brígido, Clarisse; Goss, Michael J.; Nobre, Tânia (Frontiers in Microbiology, 2018)
The symbiosis established between arbuscular mycorrhizal fungi (AMF) and roots of most land plants plays a key role in plant nutrient acquisition and alleviation of environmental stresses. Despite the ubiquity of the symbiosis, AMF and host species display significant specificity in their interactions. To clarify preferential associations between wheat (Triticum aestivum) and AMF, we characterized root AMF communities in the transition from two first host species, ryegrass (Lolium rigidum) and yellow-serradella (Ornithopus compressus), grown separately or together, to a second host (wheat), by sequencing the large subunit ribosomal DNA (LSU rDNA) gene. The response of AMF communities in wheat to prior soil disturbance – and consequently of the mycelial network [intact extraradical mycelium (ERM) vs. disrupted mycelium] established with either of the first hosts – was also investigated. Since the outcome of a specific host–symbiont interaction depends on the molecular responses of the host plant upon microbial colonization, we studied the expression of six key symbiosis-related genes in wheat roots. AMF communities on L. rigidum and O. compressus roots were clearly distinct. Within an undisturbed ERM, wheat AMF communities were similar to that of previous host, and O. compressus-wheat-AMF interactions supported a greater growth of wheat than L. rigidum-wheat-AMF interactions. This effect declined when ERM was disrupted, but generated a greater activation of symbiotic genes in wheat, indicating that plant symbiotic program depends on some extent on the colonizing symbiont propagule type. When a mixture of L. rigidum and O. compressus was planted, the wheat colonization pattern resembled that of O. compressus, although this was not reflected in a greater growth. These results show a lasting effect of previous hosts in shaping wheat AMF communities through an efficient use of the established ERM, although not completely obliterating host–symbiont specificity.